Murky Images. The Poetics of Intertextual Dissonance in the Apocryphal Films of Andrei Zviagyntsev - Pawłowska-Jądrzyk, Brygida (Załącznik Kulturoznawczy, 2023)
The first two films of Andrei Zvyagintsev, The Return and The Banishment, deserve to be called modern apocrypha, as they methodically and comprehensively utilise elements of Christian symbolism and are part of the non-canonical dialogue with religious messages. The films are characterised by a multiplicity of thematic plans that are outlined mainly through a variety of intertextual references. Among these relationships, a particular place is occupied by biblical and evangelical references, which are mostly mediated by artistic intertexts (especially paintings). The Russian director entangles the viewer in a subtle play of meanings: he evokes canonical scenes and stories, but distorts symbolic references, multiplying and confusing further interpretive clues. In addition to (completely inconsistent) references to the works of others, intertextual tensions are shown in his work on at least two levels: between different elements or levels of a given film (the function of the photograph motif next to the rest ofthe film text) and between the various films of Zvyagintsev himself (casting the same actor in both leading roles). The talented successor to Tarkovsky follows the mystery of human fate, eager to capture the metaphysical community of critical experiences. This mystery in the work of Zvyagintsev emerges in a quite obvious way from the eternal truths established in archetypes, in biblical and evangelical wisdom. It is much easier to see it in the fusion of ‛murky imagesʼ than it is to understand.